1981
DOI: 10.1113/jphysiol.1981.sp013872
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of ion transport associated with osmotic gradients in rat small intestine.

Abstract: 1. The electrical potential difference, short-circuit current, tissue conductance, and fluxes of sodium and chloride were measured in rat small intestine in an in vitro chamber preparation in the presence and absence of 100 mM-mannitol on either the mucosal or serosal surface. 2. Mucosal mannitol generally decreased potential difference, short-circuit current, and tissue conductance while serosal mannitol increased the electrical variables. 3. Mucosal mannitol decreased unidirectional movement of sodium and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Previously, we and others (12,18) have observed that anisosmotic bathing solutions alter the G t in the small intestine. Exposure of intact jejunum to a hypertonic solution (isotonic ϩ 250 mosM) in the luminal bath decreases the G t to levels similar to that attained by cAMP i stimulation (18) and significantly limits the subsequent I sc response to increased cAMP i (see Fig.…”
Section: Stimulation Of Camp I In Full-thickness Small Intestinal Prep-mentioning
confidence: 97%
“…Previously, we and others (12,18) have observed that anisosmotic bathing solutions alter the G t in the small intestine. Exposure of intact jejunum to a hypertonic solution (isotonic ϩ 250 mosM) in the luminal bath decreases the G t to levels similar to that attained by cAMP i stimulation (18) and significantly limits the subsequent I sc response to increased cAMP i (see Fig.…”
Section: Stimulation Of Camp I In Full-thickness Small Intestinal Prep-mentioning
confidence: 97%
“…changes was excluded by demonstrating that streaming p.d.s are still generated in the presence of 10-4 M-ouabain. Since Decker et al (1981) did not assay the tissue for tracer, it is also difficult to interpret their data regarding the lack of solvent drag effects. In the isolated, perfused, salamander proximal tubule, salt polarization in the unstirred layers has been excluded electrophysiologically as being responsible for streaming potentials (Boulpaep & Tripathi, 1984).…”
Section: Mechanisms Of Water Flow Across the Intestinementioning
confidence: 99%
“…changes could not be due to changes in organic solute-Na+ co-transport. The view of Decker, Jackson & Tai (1981) that active transport parameters are responsible for the p.d. changes was excluded by demonstrating that streaming p.d.s are still generated in the presence of 10-4 M-ouabain.…”
Section: Mechanisms Of Water Flow Across the Intestinementioning
confidence: 99%
“…Previous studies have shown that net movements of sodium across rat small intestine may be difficult to demonstrate due to the large passive permeability of the tissue to the ion, and because the basal rate of sodium pumping is compensated by recycling of transported sodium from the lamina propria to the mucosal fluid (Tai & Decker, 1980;Decker, Jackson & Tai, 1981). In the present experiments, the diffusive components of the sodium fluxes were decreased by use of a medium containing only 20 mM-sodium.…”
Section: Discussionmentioning
confidence: 47%
“…It has been reported that 5 x 1O-4 M-acetazolamide almost totally inhibits the activity of the enzyme in intact cells (Maren, 1977). Thus, the finding that the transport of weak electrolytes was not inhibited by this concentration of the inhibitor does not support the suggestion that the alkalinization process may be ascribed to transport of metabolic bicarbonate; (ii) calculations based on published data for intestinal metabolism (see for example, Jackson & Kutcher, 1977) show that the level of endogenous CO2 production is inadequate, by at least one order of magnitude, to provide the level of buffering in the epithelial lateral interspace necessary to support the observed rate of weak electrolyte transport; (iii) analysis of the electrical correlates of electrolyte fluxes across rat small intestine in vitro indicates that metabolic bicarbonate moves from the epithelial cells into the mucosal fluid (Tai & Decker, 1981), and not into the serosal fluid as would be required if bicarbonate were to play a significant role in alkalinizing the lateral interspace. For these reasons the possibility that alkalinization ofthe lateral interspace may be associated with transport of exogenous, or metabolic bicarbonate was considered to be improbable, and this suggested that proton or hydroxyl ion translocating mechanisms at the basolateral membrane required further examination.…”
Section: Discussionmentioning
confidence: 99%